Patterns of relationships between learners and educators in the perspective of contemporary Islamic philosophy - Sania, Fitri; Sirozi, Muhammad (Journal of Research in Instructional, 2025)
This article examines the pattern of relations between learners and educators in the context of contemporary Islamic education philosophy. By highlighting the thoughts of prominent figures such as Seyyed Hossein Nasr, Fazlur Rahman, Syed Muhammad Naquib al-Attas, Ismail Raji al-Faruqi, and Taha Jabir al-Alwani, this article discusses the concept of relationship patterns such as adab, critical dialogue, holistic education, integration of knowledge, and ijtihad. This research aims to explain the ideal relationship pattern between learners and educators in contemporary Islamic education through a relationship pattern that is mutually respectful and dialogical, focusing on character building, spirituality, and learners' critical thinking. This research method uses descriptive qualitative research using the library research method, data sources taken from books, website articles, and the Qur'an, then analyzed to conclude. The results show that contemporary muslim intellectuals such as Seyyed Hossein Nasr, Fazlur Rahman, Syed Muhammad Naquib al-Attas, Ismail Raji al-Faruqi, and Taha Jabir al-Alwani affirm that the pattern of relations between learners and educators must be based on substantial respect for the epistemology and authority of educators while facilitating the independent and critical development of learners in the pedagogical process. This aims to form learners with intellectual capabilities, moral integrity, and spirituality.